Removal of pharmaceuticals, polybrominated flame retardants and UV-filters from sludge by the fungus Trametes versicolor in bioslurry reactor - Rodríguez Rodríguez, Carlos E. (2012)
Conventional wastewater treatments are inefficient in the removal of many organic pollutants. The pres ence of these contaminants in the final sludge represents a source of environmental pollution due to the increasing use of biosolids in land application. A biotechnological approach which employed the fun gus Trametes versicolor in a sludge-bioslurry reactor was assessed in order to remove several groups of emerging pollutants. Biological fungal activity was monitored by means of ergosterol and laccase deter minations. Fifteen out of 24 detected pharmaceuticals were removed at efficiencies over 50% after the treatment, including eight completely degraded. Removal ranged between 16–53% and 22–100% for the brominated flame retardants and the UV-filters, respectively. Only two of all the detected compounds remained unchanged after the treatment. Although elimination results are promising, the toxicity of the final sludge increased after the treatment. This finding is contrary to the toxicity results obtained in similar treatments of sludge with T. versicolor in solid-phase.